Carbon‐Nanotube‐Bridging Strategy for Integrating Single Fe Atoms and NiCo Nanoparticles in a Bifunctional Oxygen Electrocatalyst toward High‐Efficiency and Long‐Life Rechargeable Zinc–Air Batteries - Ding, Shichao; He, Lin; Fang, Lingzhe; Zhu, Yuanzhi; Li, Tao; Lyu, Zhaoyuan; Du, Dan; Lin, Yuehe; Li, Jin‐Cheng (Advanced energy materials, 2022)
The development of highly efficient and robust bifunctional electrocatalysts for oxygen reduction (ORR) and evolution reactions (OER) is the key issue for realizing high‐performance and long‐life rechargeable zinc–air batteries (ZABs). However, it is still a great challenge to integrate independent ORR and OER sites in a catalyst with high activity. Here, a carbon nanotube‐bridging strategy is proposed to synthesize such a bifunctional oxygen electrocatalyst enriched with highly active single‐atom Fe sites for the ORR and high‐performance nanosized NiCo hydroxides for the OER. Consequently, the developed catalyst shows a small overpotential difference of 0.686 V. When used as an oxygen electrode catalyst, the corresponding ZAB exhibits a large power density of 219.5 mW cm−2, a small charge–discharge voltage gap of 0.72 V at 10 mA cm−2, and outstanding discharge–charge durability without attenuation after more than 700 cycles. This work proposes a new idea to realize multifunctional catalysts and drives the practical application of ZABs. A bifunctional oxygen electrocatalyst is designed by a carbon nanotube–bridged strategy enriched with ultrahigh–activity single–atom Fe sites and nanosized NiCo hydroxides for excellent oxygen reduction and evolution. Such a bifunctional oxygen electrocatalyst assembled rechargeable zinc‐air batters exhibit a large power density, a small charge‐discharge voltage gap, and outstanding discharge‐charge durability.